Analisis Dan Inventarisasi Famili Annonaceae Di Perumahan Gading Junti Asri, Desa Sangkanhurip, Kabupaten Bandung - Pavitaningrum, Candramurti; Kamila, Chiquita; Supriyatna, Ateng (Universitas Gajah Putih, 2023)
The Annonaceae family is generally known as the Soursop family, which has a distribution of around 128 genera and consists of approximately 2,300 species. Annonaceae have lifeforms from bushes to trees. The family produces fruit and various other benefits. Anonnaceae family is commonly found on the Australian continent, the Asian continent, the Americas, and the African continent and tropical climates but is rarely in areas with sub-tropical climates. This descriptive study has conducted at the Gading Junti Asri Housing Complex, Sangkanhurip Village, Bandung Regency. The tool used is a smartphone camera. The materials used are identified Annonaceae plant species around the residential area of ​​Gading Junti Asri. The data used to describe is descriptive qualitative data generated by reading, studying, and reviewing literature related to morphology, taxonomy, and the benefits of plants from the Anonnaceae family found based on observations at Gading Junti Asri Housing, Sangkanhurip Village, Bandung Regency. there are five Soursop trees (Annona muricata L.) and one Srikaya tree (Annona squamosa L.). These plants have a similar morphology and live well in tropical climates. These plants have a variety of uses besides their fruit-eaten parts of trees are also beneficial in the medical field, especially pharmacology.